Tax Risks in the Company’s Accounting System: Essence, Identification and Control - Shtiller, Marina V.; Nazarova, Vera L.; Selezneva, Irina V.; Kogut, Oksana Yu.; Bekenova, Lilia M.; Jondelbayeva, Aygul S.; Korvyakov, Valeri A. (International Journal of Economics and Financial Issues, 2016)
The article considers issues on reduction of the tax risk in the framework of management accounting. The main characteristics that are inherent in tax risk have been determined; taxpayers’ behavior patterns have been distinguished. The authors have examined the relationship of tax planning and tax risk and determined its particular importance in order to reduce tax risk. Modern problems of management of company’s tax risks as an integral part of the common management decision-making system have been also considered. The necessity of scientific research, the use of different methods of reducing tax risks in the company, the development of risk management strategies in the form of risk prediction have been proved. Tax risk functions have been identified and measures of their accounting, in order to reduce tax risks have been proposed. The main principles of tax risks assessment associated with the concept of acceptable risk, specifying risk threshold amount, and calculation of the value of economic damage of indicators that are necessary for risk management have been revealed. Keywords: Risk Management, Tax Planning, Tax Risk JEL Classification: F15; M41; G15